Tourism and the irony of colonial underdevelopment in Nhất Linh's "Going to the West". Issue 4 (2nd October 2018) - Nguyen, Duy Lap
ABSTRACT: This essay proposes a reading of Nhất Linh's "Going to the West" ( Đi Tây, 1935). The travelogue presents a critique of colonialism that was prevalent among the interwar Vietnamese elite. In the narrative, the voyage to France provides the pretext for a political comedy, ironising an imperialism that proclaimed equality in the metropole, while perpetuating colonial underdevelopment. This irony is highlighted in a series of contrasts between the condition of Vietnamese servants or "boys" and that of their metropolitan counterparts: waiters in the restaurant industry. In the travelogue, this commodified form of consumption, which colonised everyday life in France, becomes the occasion for a critique of underdevelopment. This critique, however, presupposes the same European ideal of modernity, used to justify the colonial project. The essay concludes with a history of the "boy" as a symbol of colonial oppression, created, ironically, by the attempt to impose the Republican ideal of equality.